Ecotoxicological effect of ketoconazole on the antioxidant system of Daphnia similis - do Prado, Caio César Achiles; Queiroz, Lucas Gonçalves; da Silva, Flávio Teixeira; de Paiva, Teresa Cristina Brazil (Comparative biochemistry and physiology. Toxicology & pharmacology, 2021)
The occurrence of emerging pharmaceutical pollutants (i.e. small drugs, antibiotics) present in aquatic environments shown to be a current environmental problem still without apparent solution. In this regard, the use of ecotoxicological techniques has been shown fundamental for the appraisal of damage to affected living organisms. Herein, ecotoxicological tests were conducted, focusing on the evaluation of the effects of ketoconazole (KTZ) on the antioxidant system of the model body Daphnia similis. In order to study the biochemical changes caused by KTZ in the antioxidant system, the enzymatic biomarkers glutathione S-transferase (GST), catalase (CAT), and ascorbate peroxidase (APX) were monitored. Toxicological tests were conducted using KTZ concentrations (0–10 μg·L−1). Prolonged exposure to KTZ (336 h) caused changes upon the expression of antioxidant enzymes and simultaneously affected the reproductive system in those organisms. Moreover, a decrease in GST and APX activity was observed caused by KTZ exposure, respectively 79.2% (3.53 μmol min−1 mg−1 protein) and 24.4% (0.88 μmol min−1 mg−1 protein). On the other hand, it was observed an increase of 27% (0.17 μmol min−1 mg−1 protein) in CAT activity. Through this study, it was possible to observe the toxicological effects of KTZ, which proves its action as an oxidative stress-inducing agent and endocrine modifier in daphnids organisms. [Display omitted] •Pharmacological products present toxic risks to biota from aquatic environments.•Daphnia similis is sensitive to low doses of KTZ (<2.08 μg·L−1).•KTZ (<0.32 μg·L−1) promoted a modification in the enzymatic responses of D. similis.•KTZ toxicity showed greater damage to GST activity (79% reduction in the activity).•KTZ showed induction of reproductive activity in D. similis.